Integrasi Filsafat Dan Teori Pendidikan Islam Dalam Membangun Paradigma Pendidikan Modern - Mutatohirin; Zaenurrozi; Aminah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
Modern education, as it develops within contemporary educational discourse, is often secular in nature, lacking an adequate understanding of the spiritual-transcendental dimension that is the essence of Islamic education. Integrating Islamic educational philosophy and theory can be a solution to fill this gap, offering an approach that not only integrates knowledge (an integrated curriculum) but also harmonizes the relationship between humans, nature, and their creator (a tauhidic worldview). This study employs a qualitative approach using library research. Through a qualitative approach with a literature analysis method, this study will examine key concepts in Islamic educational philosophy, Islamic learning theory, and its relevance to the development of an educational model that combines aspects of aqliyah (intellectual), qalbiyah (spiritual-emotional), and amaliyah (practical-social). The results of this study indicate that to understand the meaning and essence of education itself, it needs to be supported by a philosophical approach, especially in the context of understanding the philosophy of science which contains ontology, epistemology, and axiology. Therefore, a theory or approaches are needed to find out more about what education should be studied in Islam. However, the discussion in Islam itself is very broad in context and scope, so a development theory is needed that is in accordance with the needs of the times, so that Islam itself is not left behind and is not considered a backward religion.